L-carnitine supplementation decreases post-exercise blood lactate levels and enhances aerobic capacity in trained individuals: systematic review and meta-analysis - Fukata, E.; Pribadi, H. P.; Sugiarto, D. (Trends in Sport Sciences, 2024)
Introduction. A benefit of L-carnitine (LC) supplementation for athletes` performance remains unclear. The present study aimed to evaluate an effect of LC supplementation on a post-exercise blood lactate level and aerobic capacity in athletes/trained individuals. Methods. A systematic review and meta-analysis study was conducted based on the PRISMA guidelines. PubMed, Google Scholar, and ProQuest were searched for relevant studies from database inception to November 2023. An overall effects estimation was performed using random and fixed effects models for a blood lactate level and maximal oxygen consumption (VO2 max). Pooled effects were presented as standardized mean difference or mean difference. Results. A total of 257 athletes from 14 studies were included. Pooled analysis demonstrated that a supplementation group had significantly lower blood lactate levels (SMD = -0.52 mmol/L, 95% CI: -0.85 to -0.19, p = 0.002) and higher V?O2 max (MD = 2.16 ml/kg/min, 95% CI: 0.45 to 3.87, p = 0.01) compared to a placebo group. Subgroup analysis showed that chronic LC supplementation resulted in lower post-exercise blood lactate levels than placebo (SMD = -0.69 mmol/L, 95% CI: -1.16 to -0.21, p = 0.004). Conclusions. This study suggests that athletes may benefit from chronic LC supplementation by decreasing post-exercise blood lactate levels and increasing V?O2 max. However, acute LC supplementation only resulted in an increase in V?O2 max. Nevertheless, more scrutinous studies are needed to ascertain its efficacy.